PENINGKATAN KEMAMPUAN DIGITALISASI PEMASARAN PADA UMKM GULA SEMUT KELAPA DI BANYUMAS UNTUK MENINGKATKAN DAYA SAING DI ERA DIGITAL - Suwali, Suwali; Hana Afifah; Pupu Sriwulan Sumaya; Hasirun, Hasirun; Handayani, Juli Handayani; Reza Rahmadi Hasibuan (Awatara Publisher, 2024)
This community service program aims to enhance the digital marketing capabilities of coconut palm sugar SMEs in Banyumas, to strengthen their competitiveness in the digital era. Through a participatory approach, the program involved several stages: needs identification, digital marketing training, intensive mentoring, as well as monitoring and evaluation. The results showed a significant improvement in the ability of SMEs to use digital platforms such as e-commerce and social media. About 70% of participants successfully created accounts on e-commerce platforms and utilized social media to promote their products. The improvement in the quality of marketing content also led to an increase in sales and market expansion from local to national. However, challenges such as limited internet access and human resource capacity in managing digital strategies still need to be addressed. This program has enhanced the competitiveness of SMEs through packaging innovation and digital marketing but requires ongoing support from various parties, especially in terms of infrastructure and mentoring. The implications of this activity highlight the importance of digitalization as a long-term strategy for SMEs to compete in an increasingly competitive market. Therefore, collaboration between the government, educational institutions, and the private sector is crucial to support the sustainability of SME digital transformation in Banyumas.